Influence of phonotactic probability/neighbourhood density on lexical learning in late talkers. Issue 2 (9th November 2012) - MacRoy‐Higgins, Michelle; Schwartz, Richard G.; Shafer, Valerie L.; Marton, Klara
Abstract Background Toddlers who are late talkers demonstrate delays in phonological and lexical skills. However, the influence of phonological factors on lexical acquisition in toddlers who are late talkers has not been examined directly. Aims To examine the influence of phonotactic probability/neighbourhood density on word learning in toddlers who were late talkers using comprehension, production and word recognition tasks. Methods & Procedures Two‐year‐olds who were late talkers (n = 12) and typically developing toddlers (n = 12) were exposed to 12 novel pseudo‐words for unfamiliar objects in ten training sessions. Pseudo‐words contained high or low phonotactic probability English sound sequences. The toddlers' comprehension, speech production and detection of mispronunciation of the newly learned words were examined using a preferential looking paradigm. Outcomes & Results Late talkers showed poorer performance than toddlers with typical language development in all three tasks: comprehension, production and detection of mispronunciations. The toddlers with typical language development showed better speech production and more sensitivity to mispronunciations for high than low phonotactic probability/neighbourhood density sequences. Phonotactic probability/neighbourhood density did not influence the late talkers' speech production or sensitivity to mispronunciations; they performed similarly for pseudo‐words with high and low phonotactic probability/neighbourhood density sound sequences. Conclusions & Implications The results indicate that some late talkers do not recognize statistical properties of their language, which may contribute to their slower lexical learning.